The 6th International Electronic Conference on Sensors and Applications 2020
DOI: 10.3390/ecsa-6-06637
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a WASN-Based Urban Acoustic Dataset for the Dynamic Mapping of Road Traffic Noise

Abstract: Road Traffic Noise (RTN) is one of the main pollutants in urban and suburban areas, negatively affecting the quality of life of their inhabitants. In the context of the European LIFE DYNAMAP project, two Wireless Acoustic Sensor Networks (WASN) have been deployed to monitor RTN: one in District 9 of Milan, and another along the A90 motorway of Rome. Since the dynamic mapping system should be able to identify and remove those Anomalous Noise Events (ANEs) unrelated to regular road traffic (e.g., sirens, horns, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…This section describes the results of the experiments from the impact analysis conducted on the two environmental WASN-based audio databases from the DYNAMAP's Milan and Rome pilot areas [39,40]. According to the project specifications, the considered integration time to update the L Aeq,T values of the RTN maps is 5 min [30], i.e., T = 300 s. To analyze to what extent the collected ANEs from each sensor location bias the L Aeq,300s measurement, the impacts are categorized within three impact ranges (i.e., N R = 3) [37], accounting for those occurrences (from either individual or aggregate ANEs) causing a low-impact in θ 1 = (−∞, 0.5) dB, a medium-impact in θ 2 = [0.5, 2) dB, and, finally, a high-impact in θ 3 = [2, +∞) dB, θ 3 = θ c being as this last interval collects those cases that surpass the critical threshold γ c = 2 dB according to the WG-AEN [14].…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This section describes the results of the experiments from the impact analysis conducted on the two environmental WASN-based audio databases from the DYNAMAP's Milan and Rome pilot areas [39,40]. According to the project specifications, the considered integration time to update the L Aeq,T values of the RTN maps is 5 min [30], i.e., T = 300 s. To analyze to what extent the collected ANEs from each sensor location bias the L Aeq,300s measurement, the impacts are categorized within three impact ranges (i.e., N R = 3) [37], accounting for those occurrences (from either individual or aggregate ANEs) causing a low-impact in θ 1 = (−∞, 0.5) dB, a medium-impact in θ 2 = [0.5, 2) dB, and, finally, a high-impact in θ 3 = [2, +∞) dB, θ 3 = θ c being as this last interval collects those cases that surpass the critical threshold γ c = 2 dB according to the WG-AEN [14].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The analysis of those datasets showed the highly local and unpredictable nature of anomalous noise events, which were manually labeled and used to train the preliminary version of the ANED algorithm [36]. Recently, the deployment of the two WASNs in both pilot areas has led to the generation of a suburban acoustic dataset through the 19-nodes WASN in Rome [40], together with the completion of the first steps of the creation of an urban dataset through the 24-node WASN installed in Milan in real operation [39]. From these two experiences, it can be concluded that the evaluation of the acoustic salience of any environmental acoustic event is relevant in order to improve the accuracy of the derived machine listening approaches [43], an issue that was justified in [37] after evaluating the individual impact of the detected events on the overall equivalent noise level computation considering 9 h of real-life acoustic data collected through an expert-based recording campaign.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of this paper was to offer a more general approach to evaluate the performance comparison of all the implemented algorithms over the proposed scenarios. It is known from previous works that the training and test of machine learning algorithms varies substantially [ 28 ] when going to the simulations in the laboratory with a small corpus into real-operation environment, where larger corpora are used [ 29 ], and several unpredictable events can occur. This work faced only the first part of the tests, near a proof of concept of the best combination of FE and ML for each type of group of sounds.…”
Section: Introductionmentioning
confidence: 99%